2020
DOI: 10.3389/fvets.2020.575801
|View full text |Cite
|
Sign up to set email alerts
|

Phytogenic Additives Can Modulate Rumen Microbiome to Mediate Fermentation Kinetics and Methanogenesis Through Exploiting Diet–Microbe Interaction

Abstract: Ruminants inhabit the consortia of gut microbes that play a critical functional role in their maintenance and nourishment by enabling them to use cellulosic and non-cellulosic feed material. These gut microbes perform major physiological activities, including digestion and metabolism of dietary components, to derive energy to meet major protein (65–85%) and energy (ca 80%) requirements of the host. Owing to their contribution to digestive physiology, rumen microbes are considered one of the crucial factors aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 260 publications
(284 reference statements)
2
52
0
13
Order By: Relevance
“…Previous studies had shown different effects of oregano essential oil and cobalt on rumen microbial activity and fermentation characteristics in ruminants due to different additive types and adding levels [ 16 ], which may be related to the type of EO, its structure and the substrate employed. Therefore, to develop new additives for EO binding to ultimately effectively regulate ruminant production, in this study, the effects of different gradients of oregano essential oil and cobalt lactate binding on nutrient digestibility, rumen fermentation patterns and microbiota were evaluated by in vitro incubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies had shown different effects of oregano essential oil and cobalt on rumen microbial activity and fermentation characteristics in ruminants due to different additive types and adding levels [ 16 ], which may be related to the type of EO, its structure and the substrate employed. Therefore, to develop new additives for EO binding to ultimately effectively regulate ruminant production, in this study, the effects of different gradients of oregano essential oil and cobalt lactate binding on nutrient digestibility, rumen fermentation patterns and microbiota were evaluated by in vitro incubation.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments showed that providing a mixture of Co and EO improved rumen fermentation capacity and altered VFA patterns, resulting in improved digestibility of dry matter, protein and fiber. However, previous studies on oregano EO and Co have yielded inconsistent results on the basis of the amount and type of EO additive, and few studies have reported relationships between rumen microbes and rumen fermentation parameters and feed digestibility [ 16 ]. This study hypothesized that different levels of EOC addition would have different effects on rumen microorganisms, while nutrient digestibility and fermentation parameters might change with the microbiota altered.…”
Section: Introductionmentioning
confidence: 99%
“…Several agents to inhibit ruminal bacteria were evaluated in an in vitro system, and the ability to change the rumen microbiota and rumen fermentation has been shown [ 45 47 ]. Shen, Liu, Yu (47) reported that monensin and nisin supplementation decreased the absolute abundance of total bacteria and overall rumen fermentation (gas and VFA production) with a concomitant change in the major rumen microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the cervical barrier is crossed, allowing the microbial entry from the vagina or environment or skin into the genital tract (Ochiel et al, 2008). Porphyromonas, Bacteroidetes, and Fusobacterium inhabiting rumen are excreted but also add to the possibilities of uterus infection leading to metritis (Hassan et al, 2020;Wang et al, 2013). The prevalence of microbes in livestock environments can easily cross the host's defense system and establish a niche in the uterus (Baker et al, 2018).…”
Section: Reproductive-tract Microbiomementioning
confidence: 99%